2021
DOI: 10.1002/hep.31679
|View full text |Cite
|
Sign up to set email alerts
|

Farnesoid X Receptor Activation Impairs Liver Progenitor Cell–Mediated Liver Regeneration via the PTEN‐PI3K‐AKT‐mTOR Axis in Zebrafish

Abstract: BaCKgRoUND aND aIMS: Following mild liver injury, pre-existing hepatocytes replicate. However, if hepatocyte proliferation is compromised, such as in chronic liver diseases, biliary epithelial cells (BECs) contribute to hepatocytes through liver progenitor cells (LPCs), thereby restoring hepatic mass and function. Recently, augmenting innate BECdriven liver regeneration has garnered attention as an alternative to liver transplantation, the only reliable treatment for patients with end-stage liver diseases. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 51 publications
1
35
2
Order By: Relevance
“…NR0B2 gene expression had no significant correlation with PIK3CB and AKT genes (Figure 4D). These data are in agreement with a recent report showing a negative correlation between FXR/NR0B2 action and PI3K pathway in liver regeneration (38).…”
Section: Nr0b2 Expression Is Negatively Associated With Tumor-infiltrating Lymphocytes and Pi3k Genes In Liver Cancerssupporting
confidence: 94%
“…NR0B2 gene expression had no significant correlation with PIK3CB and AKT genes (Figure 4D). These data are in agreement with a recent report showing a negative correlation between FXR/NR0B2 action and PI3K pathway in liver regeneration (38).…”
Section: Nr0b2 Expression Is Negatively Associated With Tumor-infiltrating Lymphocytes and Pi3k Genes In Liver Cancerssupporting
confidence: 94%
“…Farnesoid X receptor (FXR), encoded by NR1H4 gene and expressing highly in the liver and intestine, belongs to the nuclear receptor family and takes part in regulating BA homeostasis, glucose and lipid metabolism, liver regeneration, cholestasis and hepatic fibrosis. 5–7 Chronic hepatic injury due to the excessive accumulation of BAs is considered a major culprit for the pathogenesis of HCC. 8 Previously, it was reported that mice would develop liver tumors spontaneously in the absence of FXR, 9 and whole-body loss of NR1H4 gene led to Myc and cyclin-dependent kinase 4 ( Cdk4 ) inductions and BA elevation, eventually resulting in age-dependent hepatic tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, farnesoid X receptor (FXR) has been identified as inhibitors of the alternative liver regeneration by enhancing phosphatase and tensin homolog (PTEN) activity. It has been confirmed in zebrafish that FXR activation blocks LPC-to-hepatocyte differentiation, but not BEC-to-LPC dedifferentiation [ 33 ]. Importantly, it is supposed that these pathways might be manipulated to induce LPC differentiation for treatment of patients with ESLD.…”
Section: The Alternative Liver Regenerationmentioning
confidence: 99%